Geometric range‐free distance estimation using reference anchor in wireless sensor networks. Issue 1 (1st January 2016) - Woo, Hyunjae; Lee, Chaewoo
Abstract : A geometric distance estimation algorithm based on the reference anchor is proposed. Geometric distance estimation is widely used to estimate the distance to the remote anchor. The geometric distance estimation accuracy is considerably affected by the reliability of the sides of the geometry formed by the unknown node, the reference anchor, and the remote anchor. A new reference anchor selection method to improve the reliability of the sides of the geometry is introduced, and a novel geometric distance estimation algorithm based on the reference anchor is proposed.